P-121 A new anti-emetic: olanzapine for the prevention and treatment of cancer-related nausea and vomiting. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Sutherland, Anna; Naessens, Katrien; Plugge, Emma; Burton, Martin; Ware, Lynda; Head, Karen; Wee, Bee
Abstract : We undertook a new Cochrane Systematic Review to assess the efficacy and safety of oral olanzapine when used as an anti-emetic in the prevention and treatment of nausea and vomiting related to cancer in adults. We searched published and unpublished trials up to the 8th September 2017. We included randomised controlled trials (RCTs) of olanzapine with or without adjunct therapies for the prevention and/or treatment of nausea or vomiting in patients with cancer aged 18 or over, in any setting, with ≥10 participants per treatment arm. Standard Cochrane methodology was used. We included 14 RCTs (1917 participants) from high, middle and low income countries in which olanzapine was administered orally, in people with over 24 different cancers, none of which were funded by pharmaceutical companies. Participants received: highly emetogenic (HEC) or moderately emetogenic (MEC) chemotherapy (12 studies); chemoradiotherapy (one study); or no active treatment (one study). Eight studies await classification and 13 are ongoing. The majority of studies were at low or unclear risk of bias across most domains. A high risk of bias, related to issues of blinding, was present in 10 RCTs. Oral olanzapine probably almost doubles the likelihood of freedom from nausea and vomiting during chemotherapy from 25% to 50% (RR 1.98, 95% CI 1.59 to 2.47; 561 participants; solid tumours; HEC or MEC therapy; moderate quality evidence) when added to standard therapy. Number Needed to Treat for additional benefit (NNTB) was 5 (95% CI 3.3–6.6). Serious concerns have been raised regarding the efficacy and safety of injectable olanzapine (intravenous, intramuscular or subcutaneous). Olanzapine probably increases somnolence and fatigue compared to no treatment or placebo (RR 2.33, 95% CI 1.30 to 4.18; anticipated absolute risk 8.2% more). It is unclear if anti-emetic efficacy differs between 5 mg and 10 mg doses.